Conserved Salt Bridges Facilitate Assembly of the Helical Core Export Apparatus of a Salmonella enterica Type III Secretion System. Issue 19 (17th September 2021) - Singh, Nidhi; Kronenberger, Thales; Eipper, Andrea; Weichel, Felix; Franz-Wachtel, Mirita; Macek, Boris; Wagner, Samuel
Graphical abstract: Highlights: Salt bridges are conserved in hydrophobic core export apparatus of bacterial T3SS. Salt bridges facilitate incorporation of following subunit into helical complex. Conserved charged residues may play a role in gating of the export apparatus. Insight in delicate requirements of assembly and function of unique helical complex. Abstract: Virulence-associated type III secretion systems (T3SS) are utilized by Gram negative bacterial pathogens for injection of effector proteins into eukaryotic host cells. The transmembrane export apparatus at the core of T3SS is composed of a unique helical complex of the hydrophobic proteins SctR, SctS, SctT, and SctU. These components comprise a number of highly conserved charged residues within their hydrophobic domains. The structure of the closed state of the core complex SctR5 S4 T1 revealed that several of these residues form inter- and intramolecular salt bridges, some of which have to be broken for pore opening. Mutagenesis of individual residues was shown to compromise assembly or secretion of both, the virulence-associated and the related flagellar T3SS. However, the exact role of these conserved charged residues in the assembly and function of T3SS remains elusive. Here we performed an in-depth mutagenesis analysis of these residues in the T3SS of Salmonella Typhimurium, coupled to blue native PAGE, in vivo photocrosslinking and luciferase-based secretion assays. Our data show that these conserved salt bridges are not critical for assembly of the respective protein but rather facilitate the incorporation of the following subunit into the assembling complex. Our data also indicate that these conserved charged residues are critical for type III-dependent secretion and reveal a functional link between SctSE44 and SctTR204 and the cytoplasmic domain of SctU in gating the T3SS injectisome. Overall, our analysis provides an unprecedented insight into the delicate requirements for the assembly and function of the machinery at the core of T3SS.